Tajhizul Mayit: Pembinaan Adab Dan Tata Cara Perawatan Jenazah Dalam Islam - Doni Saputra; Ida Ansori; Wildan Habibi; Subakir; Fadhil Akbar (LP3M IAIFA Kediri, 2026)
This study aims to analyze the limited understanding of the Sari Rejo community regarding Islamic funeral rites, particularly the proper procedure for bathing the deceased. Field findings revealed that women were still directly involved in bathing male corpses, which contradicts Islamic jurisprudence (fiqh al-janāʾiz). To address this issue, the research employed the Participatory Action Research (PAR) method, engaging the community actively in every stage, from problem identification, planning, implementation, to collective reflection. Data were collected through observation, interviews, and documentation, and were analyzed using a descriptive qualitative approach.The results indicate that the community demonstrated high enthusiasm in attending funeral management training; however, their basic knowledge of funeral jurisprudence remained limited. Through the implementation of PAR, the community not only gained theoretical knowledge but also hands-on practical experience, enabling them to correct previous mistakes in practice. Furthermore, this research highlights the significant role of religious leaders in providing continuous guidance and sustainable community mentoring.The implications of this study emphasize the necessity of ongoing education and local cadre development so that the community can independently manage funeral rites in accordance with Islamic teachings. These findings are consistent with previous studies on the gap between knowledge and practice in rural funeral management and the effectiveness of practical learning in Islamic education.